Coarticulatory Aspects of the Fluent Speech of French and Italian People Who Stutter Under Altered Auditory Feedback - Verdurand, Marine; Rossato, Solange; Zmarich, Claudio (Frontiers in Psychology, 2020)
A number of studies have shown that phonetic peculiarities, especially at the coarticulation level, exist in the disfluent as well as in the perceptively fluent speech of people who stutter (PWS). However, results from fluent speech are disparate and not easily interpretable. Are the coarticulatory features a manifestation of the disorder, or rather a compensation for the disorder itself? Our purpose is to investigate the coarticulatory behavior in the fluent speech of PWS in the attempt to answer the question on its symptomatic or adaptive nature. In order to achieve this, we have studied the speech of 21 adult PWS (10 French and 11 Italian) compared to that of 20 fluent adults (10 French and 10 Italian). The participants had to repeat simple CV syllables in short carrier sentences, where C = /b, d, g/ and V = /a, i, u/. Crucially, this repetition task was performed under a condition with normal auditory feedback (NAF) for both the groups, and under a fluency-enhancing condition (only for PWS) due to an altered auditory feedback (AAF). The degree of coarticulation was measured by means of the Locus Equations (LE). Under NAF conditions, the coarticulation degree observed in fluent PWS speech is lower than that of the PWNS, and, more importantly, in AAF condition, PWS coarticulation appears even weaker than in the NAF condition. The latter result allows to interpret the low degree of coarticulation found in fluent speech of PWS under NAF condition as a compensation for the disorder, based on the fact that coarticulation is weaker in fluency-enhancing conditions. Since a lower degree of coarticulation is associated to a greater separation between the places of articulation of the consonant and the vowel, these results are compatible with the hypothesis that larger articulatory movements could be responsible for the stabilization of the PWS speech motor system, increasing the kinesthetic feedback from the effector system. This interpretation shares with a number of relatively recent proposal the idea that stuttering derives from an impaired feedforward (open-loop) control system, which makes PWS rely more heavily on a feedback-based (closed loop) motor control strategy